Uterine Inversion Complicated by Air Embolism: An Autopsy Case - Jong-Pil Park; Bongwoo Lee (Korean Journal of Legal Medicine, 2026)
Uterine inversion is a rare but life-threatening obstetric complication in which the uterine corpus turns inside and protrudes into the uterine cavity or beyond the cervix following delivery. Without immediate intervention, severe postpartum hemorrhage and hypovolemic shock can lead to fatal outcomes. Although most cases are managed manually, surgical intervention may be required in certain instances. Air embolism in obstetrics is primarily associated with surgical procedures, and its occurrence in conjunction with uterine inversion is extremely rare. This report describes the case of a 26-year-old woman who succumbed to fatal air embolism following manual reduction of an acute complete uterine inversion that occurred immediately after vaginal delivery at 36 weeks of gestation. It includes a detailed case analysis and comprehensive review of the relevant literature.